2015
DOI: 10.1017/s0950268815000291
|View full text |Cite
|
Sign up to set email alerts
|

A history of bovine tuberculosis eradication policy in Northern Ireland

Abstract: Despite many years of state-sponsored efforts to eradicate the disease from cattle through testing and slaughter, bovine tuberculosis (bTB) is still regarded as the most important and complex of animal health challenges facing the British livestock agricultural industry. This paper provides a historical analysis of the ongoing bTB statutory eradication programme in one part of the UK - Northern Ireland (NI) - which began in 1949 as a voluntary scheme, but between 1959 and 1960 became compulsory for all cattle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…For many, bTB is an everyday ubiquity, part of everyday farming life, and something to be coped with, and tolerated, rather than driven relentlessly towards elimination. This attitude markedly contrasts with the attitude at the end of the very successful first decade of the statutory programme in the late 1960s, when it was believed that bTB in N. Ireland was a problem of the past (Robinson ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For many, bTB is an everyday ubiquity, part of everyday farming life, and something to be coped with, and tolerated, rather than driven relentlessly towards elimination. This attitude markedly contrasts with the attitude at the end of the very successful first decade of the statutory programme in the late 1960s, when it was believed that bTB in N. Ireland was a problem of the past (Robinson ).…”
Section: Discussionmentioning
confidence: 90%
“…Within the European Union (EU), legislation requires the eradication of bTB from the territories of member states, primarily to facilitate the free trade of animals and animal products, but also traditionally and historically to protect human health. The statutory programme in Northern Ireland (N. Ireland) began in 1959 with the aim of eradicating the disease (see Robinson ), but nearly six decades later, bTB remains an expensive and frustrating problem for cattle farmers, state veterinary authorities, politicians and policy‐makers. All cattle are required by legislation to be tested at least annually for the disease at the state's expense, and positive animals are removed for slaughter with compensation to affected herd owners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How important are the attitudes and behaviours of farmers in relation to statutory disease control? Historically, Robinson (2015) has shown that praise was showered upon farmers by state authorities in N. Ireland when progress was made towards eradication in the early years of the statutory scheme which had started in 1959, but this changed to apportioning blame in the mid-1970s. An influential audit report (NIAO, 2009) described how a minority of farmers in N. Ireland had not complied with legislative requirements on bTB testing, or had been involved in fraudulent activity such as deliberately interfering with the skin test sites on animals to reduce or create skin swellings.…”
Section: Blaming Farmers For Ongoing Btb Spreadmentioning
confidence: 99%
“…While the unique history of the badger/bTB situation in Northern Ireland has been investigated, the critical experiences of people in the South West of England have yet to be documented. 42 Given that social research on bTB also points towards disjuncts in communication, engagement, responsibility, power and trust between central government and local actors as a key problem for bTB policy, the need to understand such histories is even more urgent. My work has also uncovered a further gap in the historiography of bTBwhile late nineteenth-and early twentieth-century debates have been extensively investigated, and this volume traces the situation since the mid-1960s, we still have a rather sketchy understanding of how the disease was (mostly) brought under control in the post-war period.…”
Section: Some Questions and Suggestionsmentioning
confidence: 99%